2017
DOI: 10.2147/jmdh.s140042
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of interprofessional collaboration on the quality of care: a case report from a small-scale resource limited health care environment

Abstract: BackgroundA critical assessment of current health care practices, as well as the training needs of various health care providers, is crucial for improving patient care. Several approaches have been proposed for defining these needs with attention on communication as a key competency for effective collaboration. Taking our cultural context, resource limitations, and small-scale setting into account, we researched the applicability of a mixed focus group approach for analysis of the communication between doctors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 20 publications
5
58
0
1
Order By: Relevance
“…15 As reported by us and others, respect and open communication were apparently an essential component of levelling hierarchy and promoting healthy and productive work environments. 2,15 Regarding personal development, the topics mentioned by the participants (i.e. leadership in practice, insight into own and other responsibilities, and personal development) corroborated earlier recommendations indicating their relevance and importance for effective team performance.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…15 As reported by us and others, respect and open communication were apparently an essential component of levelling hierarchy and promoting healthy and productive work environments. 2,15 Regarding personal development, the topics mentioned by the participants (i.e. leadership in practice, insight into own and other responsibilities, and personal development) corroborated earlier recommendations indicating their relevance and importance for effective team performance.…”
Section: Discussionsupporting
confidence: 74%
“…As a first step of this healthcare improvement project, we chose a design that was based on 1) recommendations from an earlier case study we conducted on the implementation of a competency-based health system in Curaçao and on 2) the results from earlier research on interprofessional collaboration. 2,7 Decubitus (or Pressure) Ulcer was the critical healthcare issue (CHCI) that we selected for the project reported in this paper. This health condition was considered a serious health challenge for patients in SEHOS and is recognized as one of the main quality parameters of hospital care within the Dutch healthcare system.…”
Section: Healthcare Delivery In Curaçaomentioning
confidence: 99%
“…We measured patients' satisfaction by the category of services (henceforth SCS), referring, in particular, to family physicians, specialists, hospital services, and laboratories. The process of value creation in vulnerable customers is important [42], and previous research showed that competent delivery of professional health services develops trust (henceforth TRUST) in patients [43]. As a result, the final nine hypotheses were as follows: Hypothesis 8 (H8).…”
Section: The Mediating Effect Of Satisfaction By Category Of Servicesmentioning
confidence: 99%
“…Collaboration has been defined as the cooperative arrangement in which two or more parties work together towards completing a task or achieving a common goal [1]. Interprofessional collaboration (IPC) in healthcare is a partnership among diverse health professionals to provide quality care to patients, families and caregivers [2,3]. IPC utilizes both the individual and collective skills and experience of team members, allowing them to function more effectively and deliver a higher level of care than when working alone [4].…”
Section: Introductionmentioning
confidence: 99%